2019
DOI: 10.1186/s40738-019-0068-6
|View full text |Cite
|
Sign up to set email alerts
|

Use and pattern of previous care received by infertile Nigerian women

Abstract: BackgroundPrevalence of infertility in sub-Saharan Africa is high yet fertility care, its development and access is limited in resource-poor countries like Nigeria so infertile women resort to different forms of treatment. This study aimed to determine the use and pattern of previous treatments.MethodologyThis was a descriptive Cross Sectional study conducted at a tertiary hospital in North-Western Nigeria. Interviewer administered pretested questionnaires were administered to 236 consenting clients seen at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…This corroborates previous reports of increasing uptake of IVF by women who had hitherto delayed seeking orthodox treatment or infertility. [ 10 11 ] In addition, several reports have shown donor egg IVF to be a successful option of Assisted reproduction technique (ART)even for women of advanced age. [ 11 12 13 ] Our CPR of 41.6% for DO IVF treatment is comparable to other studies where CPR of 33%–55% has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…This corroborates previous reports of increasing uptake of IVF by women who had hitherto delayed seeking orthodox treatment or infertility. [ 10 11 ] In addition, several reports have shown donor egg IVF to be a successful option of Assisted reproduction technique (ART)even for women of advanced age. [ 11 12 13 ] Our CPR of 41.6% for DO IVF treatment is comparable to other studies where CPR of 33%–55% has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the initial experimental management for six-month results were reported in couples with unexplained sub-fertility and that an intermediate prognosis of natural conception is effective (3,14). We also know that female age has a prominent negative impact on fertility and the solutions are not simple, however, an alternative like validated dynamic models could predict both natural and ART-mediated in short time (15).…”
Section: Discussionmentioning
confidence: 99%
“…In India, about 10-14% of the population is faced with infertility with greater rates in urban areas where 1 out of 6 couples are affected [4]. Infertility constitutes about 50% of gynaecological consultations in developing countries and the Prevalence of infertility in sub-Saharan Africa is reported to be higher, with 10-30 % of couples affected in Nigeria [5], others reported prevalence of 20 % with equal male and female affectation [6]. In more recent study, a higher prevalence to the tune of 30-40% was reported in Sub-Saharan Africa [7].…”
Section: Introductionmentioning
confidence: 99%